Perception of users in the climacteric about integrative practices (Research, Society and Development, 2020)
The aim of the present study was to identify, on a scientific basis, the perception of women about the use of integrative practices as strategies to alleviate climacteric changes. It is an integrative literature review of the descriptive type, with a qualitative approach, the data collected through the PICo strategy and the combination of the descriptors in health sciences (DESCS) The analysis of the publications / articles was done through detailed readings and critical form of the studies in their entirety. Twelve articles published between the years 2014 and 2020 were reviewed, evaluating the perception of women regarding integrative practices. Two themes emerged from the thematic analysis: Category 1. The (un) knowledge of women in relation to the climacteric and the use of integrative practices as a form of treatment.; Category 2. The nurses' lack of preparation and the lack of basic health service strategies to deal with climacteric women. It was evidenced that several factors hinder the introduction and use of complementary therapies as a way of treating climacteric symptoms, showing that public actions are needed to provide information to users and a better preparation of the health system.